2020
DOI: 10.1038/s41598-020-61982-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolite biomarkers in serum of rats exposed to chlorpyrifos and cadmium

Abstract: Chlorpyrifos (CPF) and cadmium (Cd) are widespread environmental pollutants, which are often present in drinking water and foods. However, the combined effects of CPF and Cd were not entirely clear at present. There was also no biomarker available to diagnose the poisoning of the two chemicals at low dose for long-term exposures. In this study, we investigated the change of serum metabolites of rats with subchronic exposure to CPF, Cd, and CPF plus Cd using gas chromatography-mass spectrometerbased metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…40 In mammals, the presence of free aminomalonate can be associated to the alkaline hydrolysis of proteins 41 and has been described as an indicator for metabolic disorders. 42,43 As shown here, the successful production of 6 and 7 in A. niger revealed that aminomalonate was readily available as well in this non-sphingofungin producing species, suggesting the existence of a biosynthetic process to produce aminomalonate also in fungi.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…40 In mammals, the presence of free aminomalonate can be associated to the alkaline hydrolysis of proteins 41 and has been described as an indicator for metabolic disorders. 42,43 As shown here, the successful production of 6 and 7 in A. niger revealed that aminomalonate was readily available as well in this non-sphingofungin producing species, suggesting the existence of a biosynthetic process to produce aminomalonate also in fungi.…”
Section: Resultssupporting
confidence: 60%
“…The presence of aminomalonate in living organisms has long been known and aminomalonate has been reported to be incorporated as acyl-CoA extender units in the biosynthesis of some bacterial polyketides and non-ribosomal peptides. , The formation of aminomalonate as an aminomalonyl-ACP extender unit may occur by the carboxylation of acetyl- and crotonyl-CoA and through the posttranslational modification of serine to aminomalonate by radical S-adenosyl-methionine enzymes . In mammals, the presence of free aminomalonate can be associated to the alkaline hydrolysis of proteins and has been described as an indicator for metabolic disorders. , As shown here, the successful production of 6 and 7 in A. niger revealed that aminomalonate was readily available as well in this non-sphingofungin producing species, suggesting the existence of a biosynthetic process to produce aminomalonate also in fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Toxic heavy metals can inhibit many enzymatic activities, which can cause serious damage to the reproductive, cardiovascular, and nervous systems (Zhai et al, 2015). Cd is very toxic and probably carcinogenic at low concentrations because of its very long half-life (Xu et al, 2020). Hg is a global health threat and causes impairments in the human nervous system (Karthikeyan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Aminomalonic acid strongly inhibits L-asparagine synthase activity, and is up-regulated in the urine of anxiety and major depressive disorders-diagnosed individuals [ 47 ]. Multiple metabolomic investigations also revealed that altered serum aminomalonic acid concentration was closely correlated with neuropsychiatric disorders, ketamine overdose, and aortic aneurysm [ 48 ], thus forming a link between aminomalonic acid and various diseases and toxicities. This study revealed that aminomalonic acid can serve as a potential indicator of Tac-mediated neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%